Removal of Reactive Black Dye in Water by Magnetic Mesoporous Carbon from Macadamia Nutshell - Sakonsupa Damdib; Nuttamon Vanichsetakul; Phanuwat Pimpapoat; Sergey Mikhalovsky; Rosa Busquets; Adisak Siyasukh; Nattaporn Tonanon (Adsorption Science & Technology, 2022)
The novel and intriguing role of Fe(NO3)3 as a chemical activator in carbonization of macadamia nutshell is introduced in this work. Magnetic mesoporous carbon was achieved by chemical activation of macadamia nutshell with Fe(NO3)3 under nitrogen atmosphere at 850°C (MMC-850). Porosity of MMC-850 included SBET 317 m2/g with Vmicro 0.0796 cm3/g and considerably high Vmeso 0.4318 cm3/g. Not only did MMC-850 possesses good magnetic properties with saturation magnetization and coercive force of 31.48 emu/g and 506.6 Oe, respectively, but MMC-850 also showed high-removal efficiency of reactive black dye (RB5) with maximum adsorption capacity at 123.51 mg/g. The experimental data fit the Langmuir isotherm and Elovich model. Thermal regeneration was effective in degrading RB5 and removal ability was above 90% after two regeneration cycles. RB5 removal from water by MMC-850 as an adsorbent is considered a facile and inexpensive method since macadamia nutshell is a food by-product which is a green and renewable carbon precursor. MMC-850 is a potential adsorbent because it can be separated from wastewater treatment system using magnetic force. Besides, MMC-850 particle is not brittle compared to other porous biochar/activated carbon with similar size; therefore, it is an excellent candidate for column packing or scaling up for wastewater treatment facilities in the future.